THE ROLE OF INFLUENCERS IN FORMING POLITICAL OPINION AMONG ELECTION VOTERS IN MEDAN CITY - Nadra Husna Harahap; Anang Anas Azhar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the role of influencers in shaping political opinions among voters in the city of Medan. With the increasing use of social media as a source of political information, this study highlights how platforms such as TikTok influence political perceptions and attitudes. This study uses a descriptive qualitative approach, utilizing a case study on the TikTok platform. The results of this study indicate that influencers are not only information providers, but also agents of social change and communication bridges between politicians and the public. The importance of this study is considering that now is the era of everyone using social media platforms, the presence of this study can provide guidance for politicians, political parties, and campaign teams to use influencers strategically and ethically in reaching voters in the election. TikTok is the dominant platform for obtaining political information, while influencers show a critical attitude by verifying the truth of the news received. The conclusion of this study confirms that social media has a significant impact on shaping political opinions. with good digital literacy being the main factor in filtering accurate and reliable information. However, there are challenges in the form of low political literacy and the potential for information bias. Therefore, digital literacy and critical attitudes of voters are the main factors in filtering political information. This study is expected to be a reference in a more ethical and effective political campaign strategy in the digital era.